CATEGORIZATION OF DEBRIS FLOW AND ITS PREDICTION ALONG THE HIGHWAY ROADSIDE OF DUHOK- SHEKHAN - AHMAD, HIVEEN MEQDAD (Journal of Duhok University, 2022)
Debris flow is caused by various triggers including intensive rainfall, snowmelt, and earthquakes. Quantifying the number, area, and volume of debris is critical to determine debris volume and its risks. Soil physical analysis in conjunction with laboratory geotechnical soil properties of some selected site along the highway roadsides of Duhok-Shekhan assisted in developing empirical models to predict debris flows volume from some input parameters like area, vegetation cover percent, and, the site slope. The debris flow volume was based on measuring (the length, width, and depth) of the individual debris flow sites. The results indicated that debris flows were significantly correlated with debris flow area.  In contrast, it was poorly correlated with each of the vegetation cover percentages and site slope; Furthermore, it was shown that the debris flow can be predicted with reasonable accuracy at this stage of study by an exponential model based on debris flow area only. This will enable the responsible agents to take measures to mitigate the risk of a debris flow along the highway roadsides in the study area